Parents' attitudes regarding their children's play during COVID-19: Impact of socioeconomic status and urbanicity - Leigh M. Vanderloo; Kendall Saravanamuttoo; Matthew Bourke; Shiran Zhong; Monika Szpunar; Jason Gilliland; Shauna M. Burke; Jennifer D. Irwin; Stephanie Truelove; Patricia Tucker (Elsevier, 2023)
Objectives: The COVID-19 pandemic has had a profound impact on the daily routines of parents and children. This study explored the influence of socioeconomic status (SES) and urbanicity on parents' attitudes toward their children's active play opportunities 6 months and 1.5 years into COVID-19. Methods: A sample of 239 Ontario parents of children aged 12 and younger completed two online surveys (August-December 2020; 2021) to assess parents' intentions, beliefs, and comforts concerning their child's eventual return to play, in addition to various sociodemographic and physical activity variables. Descriptive analyses were run as well as an exploratory factor analysis (EFA) was conducted to group the 14 attitude items into subscales for analysis, to ensure reliability and validity of attitude measures. Results: In general, parents in communities with more urban features (e.g., densely populated areas), single-parents, full-time employed parents, and parents with lower-incomes were more hesitant to return their children to active play during the pandemic. Conclusion: Findings from this work highlight SES and urbanicity disparities that continue to exist during COVID-19.